The Impact of European Funds on Public Expenditure in Poland - Alina Klonowska (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The main purpose of the study is to evaluate the impact of European funds on the level and structure of public expenditure in Poland. Basically, the research period covers the years 2000–2016. In pursuit of objectivity, the following hypothesis is put forth: EU funding has a significant impact on the amount and structure of public expenditure. The analysis of data on the amount of European funds supporting the state budget in Poland proves that the share of these funds in the financing of public tasks is high and the structure of public expenditures is significantly changed. In the period 2010–2015 these funds accounted for about 88% of public expenditure. It is clear that they have systematically, if gradually, risen. Over the period 2014–2015, funding exceeded 90% of total expenditure.